MENOLAK KESETARAAN: Counter-Discourse dan Motif Politik di Balik Gagasan Anti Feminisme MHTI - Ulfah, Isnatin (Musawa Jurnal Studi Gender dan Islam, 2012)
Struggle of Feminist to free up women from patriarchal domination and put them on par with men was not as expected by most women. There are Hizbut-Tahrir Indonesia (MHTI), women's subordinate HTI doing rejection. According to them, the biological nature of women different from men, and that by nature also carries implications for the different roles; women at home caring for children, men earn a living. For them Islam is very clear is appeasement. Ideas and discourses of gender equality is a Western conspiracy to destroy Islam through the women and families. From a historical perspective, the rejection was due to the accumulation of disappointment and trauma that so long Western domination of the Muslim world that Muslims suffered adversity, hence the anti-Western stance. From the perspective of ideologicaldoctrinal, because of their belief that Islam is perfect, so it is not necessary ideology and doctrines other than Islam. Only by returning to the Islamic Shariah and Khilafah system alone, Muslims can regain its former glory. From an epistemological perspective, the rejection was due to their highly textual understanding of the Qur'an and hadith, ignoring the historical text and interpreter. Resistant attitude can also be seen from the perspective of ecofeminism is a conservative women's group that provides a form of resistance to establish and articulate feminine roles are regarded as potential women that must be preserved